Radiation pneumonitis in lung cancer treated with volumetric modulated arc therapy - Wu, Kan; Xu, Xiao; Li, Xiadong; Wang, Jiahao; Zhu, Lucheng; Chen, Xueqin; Wang, Bing; Zhang, Minna; Xia, Bing; Ma, Shenglin (Journal of Thoracic Disease, 2018)
Background: Few studies to date have assessed the incidence of radiation pneumonitis (RP) in lung cancer patients who have been treated with volumetric modulated arc therapy (VMAT). This study is aimed at reporting the RP incidence rate and the risk factors associated with a symptomatic RP in patients with lung cancer treated with VMAT. Methods: A total of 77 consecutive lung cancer patients treated with VMAT from 2013 through 2015 were reviewed. RP severity was graded according to the Common Terminology Criteria for Adverse Events (CTCEA) v.4. Univariate and multivariate analyses were performed to identify the significant factors associated with RP. Results: VMAT allowed us to achieve most planning objectives on the target volumes and organs at risk, for PTV V95% =96.8%±3.1%, for lung V5 =41.3%±8.7%, V10 =30.0%±7.1%, V20 =20.9%±5.7%, for heart V5 =43.2%±29.9%, for esophagus V60 =8.1%±12.9%. The maximum dose of spinal cord was 34.4±9.5 Gy. The overall incidence of symptomatic RP (grade ≥2 by CTCAE) was 28.6% in the entire cohort, and the rate of grade ≥3 RP was 11.7%. Based on the multivariate analysis, factors predictive of symptomatic RP included lung volume receiving ≥10 Gy (V10) (P=0.019) and C-reactive protein changing level (P=0.013). Conclusions: Our data showed that the incidence rate of RP was acceptable in lung cancer patients treated with VMAT. Additionally, we found that V10 might be an important factor for predicting the development of RP when VMAT was used; but this observation needs to be validated in future studies.